Waste Management in Sumur Batu Village, Central Jakarta - Budiantoro, *Harry; Madjid, Suhirman; Asaari, Masagus; Sari, Imelda; Tambuati Subing, Hesty Juni (Riwayat: Educational Journal of History and Humanities, 2022)
Waste Management in Central Jakarta, Sumur Batu Village is a program organized by the Faculty of Economics, YARSI University for one of the functions of the Tridharma of Higher Education, namely Real Business Lectures (KKN). Waste from processing domestic and industrial needs is a major problem in all regions and regions, including Sumur Batu village in Kemayoran sub-district in Central Jakarta. If garbage is disposed of carelessly, for example thrown into a river and cannot be used at all, it can become shallow for the river, even the waste can become a flood disaster for the area. In fact, properly processed waste can prevent various diseases among residents, and waste can improve the economy and welfare of the people of Sumur Batu Village. Good waste management requires community involvement and participation. In Sumur Batu village, the support and knowledge of every head of household is very important for the welfare of the family. Household waste is separated beforehand and can encourage residents to engage in various activities and creativity to improve their economy, including fertilizer production, selling inorganic waste directly to businesses or turning recycled products into recyclables themselves. to recycle. You can earn money.